Negotiations in the workplace - Hughes, Kylie; Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 1997)
This program looks at what negotiation means, how to plan for it and how to utilise effective interpersonal skills and strategies to achieve satisfactory outcomes
Copy available in VCD format
Executive producer, David Brown ; editor, Shaun Smith ; writer, Nancy Black, David Brown
Presenter : Jenny Tudor
Keywords: Negotiation; Communication skills; Negotiation in business; Work environment